2022
DOI: 10.1039/d2nr02210a
|View full text |Cite
|
Sign up to set email alerts
|

Transmigration of magnetite nanoparticles across the blood–brain barrier in a rodent model: influence of external and alternating magnetic fields

Abstract: Despite advances in neurology, drug delivery to the central nervous system is considered a challenge due to the presence of blood brain barrier (BBB). In this study, the role of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 64 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…It has been reported that high-frequency magnetic fields can activate magnetic NPs and in turn induce cell death via cytoskeletal degradation and disruption of the cell cycle at higher particle concentration and longer incubation times . In the present study (low-frequency magnetic fields), the minimal cell viability reduction at 125 μg/mL could be attributed to oxidative stress activities. At concentrations <125 μg/mL, the combination treatment leaves the healthy cells completely unaffected. Based on these findings, we used 100 μg/mL as the particle concentration to perform endothelial leakiness studies.…”
Section: Resultsmentioning
confidence: 43%
See 3 more Smart Citations
“…It has been reported that high-frequency magnetic fields can activate magnetic NPs and in turn induce cell death via cytoskeletal degradation and disruption of the cell cycle at higher particle concentration and longer incubation times . In the present study (low-frequency magnetic fields), the minimal cell viability reduction at 125 μg/mL could be attributed to oxidative stress activities. At concentrations <125 μg/mL, the combination treatment leaves the healthy cells completely unaffected. Based on these findings, we used 100 μg/mL as the particle concentration to perform endothelial leakiness studies.…”
Section: Resultsmentioning
confidence: 43%
“…50,51 Also, shear stress can cause modulation of the cytoskeleton, intercellular junctions, and vascular permeability. 42 By contrast, magneto- NdFeB magnets (which produce static magnetic fields, ∼500 mT) and PEG-coated magnetite nanocrystals (16 and 33 nm in diameter). 3 The authors proved that magneto-mechanical transduced stress can transiently disrupt endothelial adherens junctions of HUVEC monolayers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of an alternating magnetic field and an external static magnetic field enhanced MNP crossing to ∼63%, compared to ∼50% with just the external static magnetic field alone. Besides, more MNP accumulation in the mouse brain was observed when applying an alternating magnetic field, demonstrating its ability to modulate BBB permeability through the magnetic guidance of NPs . Gkountas et al demonstrated that an EMF could significantly enhance MNP delivery across the BBB.…”
Section: Permeation Mechanisms Of Nanoparticles Capable Of Crossing T...mentioning
confidence: 99%